Richard Clough Anderson papers - Anderson, Richard Clough, 1788-1826.
Correspondence and diary (1803-1826).
Microfilm of original diary in private hands.
Private
Lawyer, diplomat, and U.S. representative from Kentucky.
Collection material in Spanish, with English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Diplomats; Lawyers; Representatives, U.S. Congress -- Kentucky